Friends : The Complete Fourth Season Episodes 1-8 - Crane, David; Cox, Courteney; David Schwimmer; Lisa Kudrow; Matt Le Blanc; Matthew Perry; Jennifer Aniston (USA Warner Home Video, 1997)
When we start the show, Rachel Green comes in wearing a wedding dress after leaving her fiancées at the altar. Rachel worked at Central Perk for awhile and finally gets a job at Bloomingdale's and Ralph Lauren. She has a baby with Ross Geller and they decide to keep the baby. Ross Geller is a paleontologist, and has had three wives. His first wife, Carol, finds out she is a lesbian and is pregnant with his baby. His second wife, Emily, is crushed when he calls this new wife Rachel instead of Emily. His third wife, Rachel, happens when they get drunk and decide to get married. Ross's sister, and Rachel's best friend, Monica Geller-Bing is a chef, and finally marries Chandler Bing. Chandler Bing is Ross's best friend, and secretly dated his sister for about 6-7 months. Monica and Chandler want to have a baby after Rachel has hers, but they can't have any. They decide to adopt a baby. They are shocked to find out that the pregnant mother is having twins. Chandler's former roommate, Joey Tribbiani, is a not so bright, but sweet actor. We played on Days of Our Lives has Dr. Drake Ramoray. Monica's other former roommate, Phoebe Buffay, is a masseuse, and a singer. Her most famous song is ""Smelley Cat."" Phoebe at the end marries a guy named Mike Hanigan. Phoebe was also was a surrogate mother for her brother's triplets. Ross and Rachel find out that they love each other when Rachel is assigned to live in Paris for a job that pays a lot. Monica and Chandler decide to move to a suburban house to raise the babies. The show ends when Monica and Chandler are moving to their new house, Ross and Rachel are living together again,and Phoebe is married to Mike.
The lives, loves, and laughs of six young friends living in Manhattan.
Language(s): English
Subtitle(s): English, French, Dutch
Keywords: Romance -- Tv Series; Comedy